Microsatellite Instability and Metastatic Colorectal Cancer – A Clinical Perspective - Buchler, Tomas (Frontiers in Oncology, 2022)
Approximately 4-5% of patients with metastatic colorectal cancer (mCRC) have mismatch repair deficient (dMMR)/microsatellite instability-high (MSI-H) tumours. These tumours present challenges in the clinical practice due to variant response to fluoropyrimidine-based chemotherapy and, perhaps, also non-immunologic targeted therapies. Recently, a breakthrough in the treatment of dMMR/MSI-H mCRC has been achieved with several clinical trials showing dramatic long-term benefit of immunotherapy using checkpoint inhibitors. Nevertheless, several questions remain regarding the optimisation of immunotherapy regimens and the use of biomarkers to identify populations set to derive the greatest benefit from immunotherapy. Combination regimens and/or the use of immunotherapy as a maintenance after induction non-immunologic systemic therapy may be the way forward to improve outcomes.